Amah and the silk-winged pigeons - Cullity, Jocelyn (New Delhi : Ruba publication, 2021)
Amah and the Silk-Winged Pigeons draws on the lost histories of the women descended from African slaves who resisted English rule during the 1857 uprising in Lucknow, India. The book is about the event that triggered Queen Victoria's reign in India for almost a century, and illuminates new and important female, Muslim perspectives on what has been called the first war of Indian independence. Lucknow in 1856 is the most opulent city in India. If the English take it over, the royal family and centuries of rich, cosmopolitan culture will disappear. Amah, personal bodyguard to the King, wants to make sure this doesn't happen. Ex-Queen, Hazrat Mahal, has the money to fortify against the English. Both women are daughters of African slaves who have grown in wealth and power thanks to the reign of the Indian royal family in Lucknow. The English are a small number, compared to the native population in the city, but Lucknow has never known war. When the women decide to take on the English colonists who declare rule, what will be the ultimate price of the women's loyalty to the royal family and to the place they've grown to love?
Keywords: Fiction; Historical fiction; History